Gambaran Motif dan Beliefs pada Jamaah Asmaul Haq Rangkah Kidul Sidoarjo - Ranggi, Desta; Herani, Ika; Lestari, Sumi (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2015)
The aim of this study was overview about the motive and beliefs of individual who are member of the Asmaul Haq. The method called "amalan" has aimed to always remember God. The essence of the concept Asmaul Haq is belief. Method of research is qualitative with phenomenological research model. Data collection techniques used observation, interview, and documentation. Data was analyzed by phenomenological MouStakas (1994). There are four subjects research was selected by snowball sampling technique, consist of two male subjects and female subjects aged 21 -50 years. The results showed that the motive whose owned four subjects are same, such as wants to bring something close to the God, become people better than before. The source of drive is internal and external drive of subjects. While the beliefs of four subjects consistently shows that faith wholeheartedly againSt Asmaul Haq is a right way to the God. The beliefs of four subjects that every expectation blessed or is not blessed by God is the beSt thing. There is no doubting or loSt of beliefs who they feel. Beliefs gives positive emotion and gratification to subjects in their life.